Building Customer Engagement through Customer Experience, Customer Trust, and Customer Satisfaction in Kaligung Train Customers - Syahputra, Dicky; Murwatiningsih, Murwatiningsih (Management Analysis Journal, 2019)
Customers are getting smarter in determining transportation services that will be used to help all activities. This study aims to examine the effect of customer experience, customer trust and customer satisfaction on customer engagement. The population of this research is all the passengers of the Semarang-Brebes Kaligung Train. A sample of 160 respondents using incidental and purposive sampling techniques. Methods of data collection using questionnaires and documentation. Data analysis using Structural Equation Modeling (SEM) with IBM SPSS AMOS version 23. The results showed that customer experience affects customer trust, customer experience influences customer satisfaction, customer experience influences customer engagement, customer trust influences customer satisfaction, customer trust affect customer engagement, customer satisfaction does not significant affect customer engagement. Suggestion from this research is Kaligung Train must continue to maintain and improve services and facilities so that the experience is better. Suggestions for further research are adding other variables or other factors related to this study and using different research objects